HUBUNGAN ANTARA SELF REGULATION DENGAN FEAR OF MISSING OUT PADA SISWA KELAS XI SMA - Yanti Armilyana; Farida Herna Astuti; Dewi Rayani (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT The use of social media in daily life can have both positive and negative impacts on students, one of which is the emergence of the fear of missing out (FOMO) phenomenon, which refers to the feeling of anxiety when someone feels left behind from the activities of others on social media. One factor that is assumed to minimize this feeling is self regulation ability. This study aims to determine the relationship between self regulation and fear of missing out among eleventh-grade students at SMA Nurul Falah Perina in the 2023/2024 academic year. This research used a quantitative approach with a correlational method. The population as well as the research sample consisted of 20 students. Data collection techniques used questionnaires as the main method, while observation, documentation, and interviews were used as supporting methods. Data analysis was conducted using the Product Moment correlation formula. The results of the study showed that there was a significant negative relationship between self regulation and fear of missing out, with a correlation coefficient value of r = -0.746 at a significance level of 5%. These findings indicate that the higher the students’ self regulation ability, the lower the level of fear of missing out experienced. Conversely, lower self regulation ability is associated with higher levels of fear of missing out in social media use. ABSTRAK Penggunaan media sosial dalam kehidupan sehari-hari dapat memberikan dampak positif maupun negatif bagi siswa, salah satunya adalah munculnya fenomena fear of missing out (FOMO), yaitu perasaan cemas ketika seseorang merasa tertinggal dari aktivitas orang lain di media sosial. Salah satu faktor yang diduga dapat meminimalkan perasaan tersebut adalah kemampuan regulasi diri (self regulation). Penelitian ini bertujuan untuk mengetahui hubungan antara self regulation dengan fear of missing out pada siswa kelas XI di SMA Nurul Falah Perina Tahun Pelajaran 2023/2024. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Populasi sekaligus sampel penelitian berjumlah 20 siswa. Teknik pengumpulan data menggunakan angket sebagai metode utama, sedangkan observasi, dokumentasi, dan wawancara digunakan sebagai metode pelengkap. Analisis data dilakukan menggunakan rumus korelasi Product Moment. Hasil penelitian menunjukkan bahwa terdapat hubungan negatif yang signifikan antara self regulation dengan fear of missing out dengan nilai koefisien korelasi sebesar r = -0,746 pada taraf signifikansi 5%. Hasil tersebut menunjukkan bahwa semakin tinggi kemampuan regulasi diri siswa, maka semakin rendah tingkat fear of missing out yang dialami. Sebaliknya, semakin rendah kemampuan regulasi diri, maka semakin tinggi kecenderungan siswa mengalami fear of missing out dalam penggunaan media sosial.